Peran entrepreneur leadership terhadap innovation performance yang dimediasi oleh innovation process - Ramadhani Fuadiputra, Iqbal; Putri , Viajeng Purnama (Jurnal Ilmu Manajemen, 2023)
This research is to identify the role of entrepreneurial leadership on innovation performance mediated by the study of the innovation process in start-up companies. The research design is a survey research using a questionnaire as a research instrument. This research was conducted to examine the effect of entrepreneurial leadership on innovation performance mediated by the innovation process, especially in start-up companies located in the East Java region with a total of approximately 119 companies with approximately 20 employees in each company. This study uses a quantitative approach with data collection methods using questionnaires which will be distributed online and processed using Partial Least Square (PLS). The results of the study show that Entrepreneur Leadership has a significant effect on Innovation Performance, and there is also a significant influence on the innovation process. This study also shows that the Innovation Process is a mediating variable between Entrepreneurial Leadership and Innovation Performance. The conclusion from this study is that Entrepreneur Leadership, Innovation process, and innovation performance have a relationship between the variables based on this study.